PENGARUH FUNGISIDA TERHADAP KEANEKARAGAMAN BAKTERI TANAH DI KOTA BATU - Indah Nur Khulillah; Abdul Latief Abadi; Luqman Qurata Aini (Jurnal Tanah dan Sumberdaya Lahan, 2019)
Environmentally friendly and conventional cultivation systems that are selected and used by farmers can directly or indirectly affect microbes in the soil. Microbial population diversity can be used as a sensitive parameter to soil quality. Bacterial populations are a determining factor in ecosystems that are important because of biological and biogeochemical cycles, and heterotrophic activities. This study suggests looking at environmentally friendly (O1) and conventional (K1, K2, K3) soil bacteria on soil planted with sweet maize and function of bacteria in ecosystems. The results of this study that diversity on environmentally friendly was higher than conventional soil. The value was 1,775; while those of the conventional lands 1, 2 and 3 were 1,587; 1,245 and 1,320. In O1 soil, the most common genus was Agrobacterium and bacteria which were only found in environmentally friendly soils were Bacillus and Clostridium. Bacteria found such as O1F and O1G which were related to B. paramycoides could be used as biological agents against Cercospora leaf spot disease, B. megaterium could bind nitrate to the rhizosphere and dissolve phosphate in the soil, and B. aryabhattai which was potential as biological fertilizers and bioremediation